Study on changing hematocrit values after a 21 day stage of training (athletics) on sand of Black Sea seaside (Constanta, Romania) - Man, M. C.; Ganera, C. (Science, Movement & Health, 2018)
Background. It is known that performance athletes, in the desire to achieve the best results, seek to train themselves in the most favorable conditions for increasing sports performance. Objectives. The research aims to achieve a significant increase in the athletes' performance by modifying the values of the hematocrit, possibly by introducing into the training plan a training course on the beach, resulting in physiological and biochemical changes favorable to the effort capacity . Methods. The research was conducted on a group of 10 performance athletes during a 21-day training course on Constanta Beach. In order to accomplish this research we used the experiment method, the staticmathematical method, the graphic representation method. Results. The analysis of the data shows that after the training on the beach that, hematocrit values increase by more than 1% after training at the seafront training, thus increasing the athletes' ability to work. Conclusions: Making one or more beach training stages significantly improves the performance of runners by triggering physiological, haematological changes in the body of athletes conducive to increased performance